Keeping and breeding of the Cyclades blunt-nosed viper (Macrovipera schweizeri) - Tóth, Tamás; Sós, Endre; Gál, János (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
The Milos viper is an endangered poison-snake has been found in the eastern basin of Mediterranean Sea and in some islands of Western Cyclades. It needs to be greater protected against directly human threat and expansion. The breeding of this viper sort is very difficult in imprisonment because of its particular reproduction method (ovipar). The Milos viper belongs to those poison-snake species that could be housed more easily. Its breeding is one of the hardest tasks among those viper species have been living in the Mediterraneum, mainly because of its reproduction method. On the basis of reports of more authors about 30% of vipers males belong to the Viperidae family are barren. Namely, between of their two hemipenises neither only one, nor the other could be unfastened. In their works, authors summarize those national and international experiences related to housing, reproduction and breeding of Milos viper.